HOUSEHOLD DEBT AND INTEREST RATES: A CASE STUDY OF SOUTH AFRICA - Kgomotso Molefe; Ashley Mutezo (Acta Economica)
South African households have increased their debt uptake, even during periods when the cost of credit has increased, which runs counter to theory. The purpose of the study is to determine both households’ borrowing reactions to interest rates and the impact of credit demand on interest rates in South Africa. A quantitative approach was followed by econometric analysis of the data. The study employed the autoregressive distributive lag and vector error correction model to analyse the time-series data for the period from 1990 to 2019. The results of the study indicate both a long-run relationship and short-run causality between household debt and interest rates in South Africa. These results support theory as they confirm claims that a low interest rate environment encourages borrowing and vice versa. Policy makers and credit regulators should be alert to the effects of policy-induced changes in interest rates, which are slow to reflect on household debt and can only be witnessed in the long run. The recommendation is that households should be advised to speed up debt repayments rather than stretch themselves during periods of low interest rates. The theoretical contribution of this study is to the loanable fund’s theory and the channels of the monetary transmission mechanism. The period analysed captured most important periods, such as the end of the Apartheid era, the National Credit Act and the financial crisis.